KEHIDUPAN NELAYAN DI PESISIR AIR TAWAR BARAT DALAM KARYA SENI LUKIS - RAHMAT HIDAYAT, Drs. H. Achyar Sikumbang Drs. Erfahmi, M.Sn (Serupa The Journal of Art Education, 2014)
The social economic of the sailor with unregular salary can not face bad condition of the nature by using machine, but all them can make the sailor live greatly and always poor economic condition.This sailor daily live was packaging in paint art cosist of ten painting with title : 1) Menunggu , 2) Bermain Pasir , 3) Istanaku , 4) Persiapan Perang, 5) Menjaring, 6) Hasil Tangkapan Hari Ini, 7) Lumayan, 8) Menarik Pukat, 9) Fisherman, 10) Kapan Redanya.And then in this final examination, the writer not only take the sailor activity but also ther family such as house wife, their kids and their home show by the real daily live of those thing.The purpose of this final task is hope the govermen and the people know how the sailor dailylive, hope the govermen can increase their live in economic, education, health and other by helping and educate them.Kat kunci : Kehidupan Nelayan Di Pesisir Pantai